Revisión de modelos energéticos - Karen M. Martínez Torrico; Francisco Javier Aliaga (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2015)
– Throughout our history we have demonstrated the relationship between the decisions of energetic character, economy and the environment. For this reason is that they begin to develop and implement energetic modeling techniques as alternative tools for both the development of energy policies, and the evaluation of its effects on the economy itself. At present it has a wide range of energy models, which address issues related to the energy field from various perspectives and using different assumptions and estimation techniques. Armed with such a wide range of models, choosing the most suitable model for application in a given context is more than a science, an art that can only be carried out with knowledge about the features, attributes and weaknesses of model families existing. In this sense, the present work aims to serve as a reference for those who have aspirations to develop energy models framework.
Keywords: C01; C53; C68; C61; C63; D58; Q40; Q48; Q51; 330